Can early neurological improvement after mechanical thrombectomy be used as a surrogate for final stroke outcome?. (24th November 2018) - Soize, Sebastien; Fabre, Guillaume; Gawlitza, Matthias; Serre, Isabelle; Bakchine, Serge; Manceau, Pierre-François; Pierot, Laurent
Abstract : Background and purpose: We aimed to identify the best definition of early neurological improvement (ENI) at 2 and 24 hours after mechanical thrombectomy (MT) and determine its ability to predict a good functional outcome at 3 months. Methods: This retrospective analysis was based on a prospectively collected registry of patients treated by MT for ischemic stroke from May 2010 to March 2017. We included patients treated with stent-retrievers with National Institute of Health Stroke Scale (NIHSS) score before treatment and at 2 and/or 24 hours after treatment and modified Rankin Score (mRS) at 3 months. Receiver operating characteristic curve analysis was performed to estimate optimal thresholds for ENI at 2 and 24 hours. The relationship between optimal ENI definitions and good outcome at 3 months (mRS 0–2) was assessed by logistic regression. Results: The analysis included 246 patients. At 2 hours, the optimal threshold to predict a good outcome at 3 months was improvementin the NIHSS score of >1 point (AUC 0.83, 95% CI 0.77 to 0.87), with sensitivity and specificity 78.3% (62.2–85.7%) and 84.6% (77.2–90.3%), respectively, and OR 12.67 (95% CI 4.69 to 31.10, p<0.0001). At 24 hours, the optimal threshold was an improvementin the NIHSS score of >4 points (AUC 0.93, 95% CI 0.89 to 0.96), with sensitivity and specificity 93.8% (87.7–97.5%) and 83.2% (75.7–89.2%), respectively, and OR 391.32 (95% CI 44.43 to 3448.35, p<0.0001). Conclusions: ENI 24 hours after thrombectomy appears to be a straightforward surrogate of long-term endpoints and may have value in future research.